2022
DOI: 10.3390/curroncol29020075
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Effect of Dendritic Cells Vaccination on Survival in Glioblastoma: A Systematic Review and Meta-Analysis

Abstract: Background: Dendritic cell vaccination (DCV) strategies, thanks to a complex immune response, may flare tumor regression and improve patients’ long-term survival. This meta-analysis aims to assess the efficacy of DCV for newly diagnosed glioblastoma patients in clinical trials. Methods: The study databases, including PubMed, Web of Knowledge, Google Scholar, Scopus, and Cochrane, were searched by two blinded investigators considering eligible studies based on the following keywords: “glioblastoma multiforme”, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…As it has been shown, adding neoadjuvant treatment may increase overall survival [46]. Among the different modalities for immunotherapy in glioblastoma, dendritic cell vaccination has gathered considerable attention after some encouraging reports showing acceptable efficacy and safety levels [13]. It is well acknowledged that DC immunization improves OS in GBM patients [18,19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As it has been shown, adding neoadjuvant treatment may increase overall survival [46]. Among the different modalities for immunotherapy in glioblastoma, dendritic cell vaccination has gathered considerable attention after some encouraging reports showing acceptable efficacy and safety levels [13]. It is well acknowledged that DC immunization improves OS in GBM patients [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Adopting immunotherapy treatments for other cancers to glioblastoma is possible, and different studies have documented some benefits [6,12,13]. Other researchers have previously shown that 90 percent of GBMs have cytomegalovirus (CMV) antigens, although the normal brain does not [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nonspecific passive immunotherapy includes activated lymphocytes and macrophages. A separate group of adoptive immunotherapy is represented by live immunocompetent cells or their fractions capable of eliciting the cell-mediated immune response to tumor-associated antigens [36,37]. This kind of active specific immunotherapy will be considered in more detail.…”
Section: Vaccines As a Modern Strategy Of Immunotherapymentioning
confidence: 99%
“…Despite the development of new radiotherapy techniques, there are a few new drugs that seem to be effective and safe. Nonetheless, the prognosis remains poor [ 6 ].…”
Section: Introductionmentioning
confidence: 99%